Effect of Curing Methods on the Compressive Strength of Concrete (International Journal of Engineering and Computer Science, 2017)
Different methods are usually adopted to cure concrete. Concrete strength partly depends on the method and duration of curing. The structural use of concrete depends largely on its strength, especially compressive strength. This study uses three curing methods to determine their effects on the compressive strength and density of concrete. These methods are immersion of concrete cubes in curing tank (Ponding), covering of cubes with wet rug (Continuous wetting) and the use of polythene sheet (Water-barrier).   Laboratory experimental procedures were adopted. A total of sixty (60) cubes were cast with 1:2:4 mix ratios. The cubes were cured in the laboratory at room temperature. The results showed that the average compressive strength values for 28-day curing vary with curing methods. The cubes cured by immersion have an average compressive strength of 29.7 N/mm2 while the ones cured by wet rug and polythene sheet have average compressive strength of 26.8 and 24.7 N/mm2 respectively. The traditional curing by immersion appeared to be the best method to achieve desired concrete strength.